Characteristics of iron ore sinter with EFB addition - Purwanto, Hadi; Rozhan, Alya Naili; Mohamad, A. S.; Zakiyuddin, Ahmad (Institute of Physics Publishing, 2018)
Utilization of EFB-derived biochar in sintering of iron ore has been conducted in this work with regards to the porosity of iron sinter. EFB has been heated up in argon atmosphere to 450ºC in order to produce biochar. In the present work, the sintering process was conducted at 1150ºC with variations of biochar content from 5% to 10%. In this case, the apparent density for iron sinter shows significant decrease as the biochar addition increase. The porosity of iron sinter showed a gradual increment from 5% to 7.5% and escalated at 10% biochar content. The results of porosity and apparent density were in line with the micrograph of iron sinter.